2021
DOI: 10.3390/nu13113939
|View full text |Cite
|
Sign up to set email alerts
|

The Type of Fat in the Diet Influences Regulatory Aminopeptidases of the Renin-Angiotensin System and Stress in the Hypothalamic-Pituitary-Adrenal Axis in Adult Wistar Rats

Abstract: (1) Background: Prolonged feeding with a high-fat diet (HFD) acts as a stressor by activating the functions of the hypothalamic-pituitary-adrenal gland (HPA) stress axis, accompanied of hypertension by inducing the renin-angiotensin-aldosterone system. Angiotensinases enzymes are regulatory aminopeptidases of angiotensin metabolism, which together with the dipeptidyl peptidase IV (DPP-IV), pyroglutamyl- and tyrosyl-aminopeptidase (pGluAP, TyrAP), participate in cognitive, stress, metabolic and cardiovascular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…High‐fat diets during perinatal periods could lead to activation of the RAS system in the adult offspring rats, inducing hypertension in later life. [ 12,13 ] Notably, the renin‐angiotensin‐aldosterone system (RAAS) is well known in the body, playing critical roles in the control of body fluids and cardiovascular regulations. [ 14 ] Despite several studies demonstrated influence of perinatal insults on the RAS‐induced cardiovascular dysfunction or disorders, [ 15 ] none of data available regarding perinatal malnutrition‐affected aldosterone receptor‐related cell functional changes and mechanisms in vascular SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…High‐fat diets during perinatal periods could lead to activation of the RAS system in the adult offspring rats, inducing hypertension in later life. [ 12,13 ] Notably, the renin‐angiotensin‐aldosterone system (RAAS) is well known in the body, playing critical roles in the control of body fluids and cardiovascular regulations. [ 14 ] Despite several studies demonstrated influence of perinatal insults on the RAS‐induced cardiovascular dysfunction or disorders, [ 15 ] none of data available regarding perinatal malnutrition‐affected aldosterone receptor‐related cell functional changes and mechanisms in vascular SMCs.…”
Section: Discussionmentioning
confidence: 99%